A Comparison of Sanctions for Non-Compliance with the Disclosure of Origin Requirement in Patent Law and Its Relevance to Shari'ah Principles - Efridani Lubis; Sukamto Kusnadi; Winahyu Erwiningsih; Noor Nadher Zghair (Nusantara: Journal of Law Studies, 2026)
This article analyses how India, Brazil, Switzerland, and Indonesia design sanctions for non-compliance with origin disclosure obligations under patent law and examines their implications for fairness, administrative feasibility, and benefit-sharing. It employs a normative-doctrinal legal approach using comparative analysis based on five indicators: legal basis, relationship with access and benefit-sharing regimes, types of sanctions, institutional design, and implications for patent validity. The findings show that differences among these countries lie not primarily in the existence of disclosure obligations, but in sanction design and its normative function: safeguarding patent validity, ensuring biodiversity compliance, or promoting administrative transparency. India represents a stringent patent-enforcement model; Brazil demonstrates an integrated biodiversity-compliance model; Switzerland emphasises administrative transparency; while Indonesia remains largely declarative, without a fully operational enforcement framework. From a Shari'ah perspective, these variations reflect different applications of justice ('adl), proportionality (al-tanāsub), and the appropriateness of sanctions to the offence (al-jazā' min jins al-'amal). Disclosure obligations embody the principles of honesty (ṣidq) and trustworthiness (amānah), while effective sanctions help prevent the illegitimate exploitation of genetic resources and traditional knowledge (ghasb) and promote the public interest (maṣlaḥah 'āmmah). Based on these findings, the article proposes a post-treaty hybrid enforcement model combining differentiated enforcement, inter-institutional verification, and graduated sanctions. This model offers a proportionate approach by avoiding both normative symbolism without coercive force and automatic patent revocation. The article contributes a comparative typology of sanction design and its institutional consequences, while extending origin-disclosure scholarship through a Shari'ah-based analysis of justice and equitable benefit-sharing across diverse legal systems.